(untitled) (Revista de Ciências Agroveterinárias, 2020)
Studies of potential and yield potential are extremely important worldwide, to identify and narrow yield potential. The objective of this study was to simulate cassava yield potential and water-limited yield potential using the Simanihot model. Cassava yield gap and the planting date effect were estimated for two locations in Rio Grande do Sul, Brazil (Santa Maria and São Luiz Gonzaga). Due to weather conditions, in Santa Maria cassava cycle was defined as annual and São Luiz Gonzaga as annual and biannual. Planting dates were set from August 1st 2017 to May 1st 2018, and harvested on Jun 15th 2018. Results showed that cassava express higher yield potential on early planting (August 10th), achieving 64.6 Mg ha-1 and 50.2 Mg ha-1 of tuber roots and 47.3 Mg ha-1 and 38.9 Mg ha-1 of aboveground biomass, in São Luiz Gonzaga and Santa Maria, respectively. Planting dates after the beginning of the climatic risk zoning, present a yield reduction of 0.364 Mg ha-1 in São Luiz Gonzaga and 0.282 Mg ha-1 in Santa Maria, for each day of delay on the planting date. These results indicate that planting cassava during the first ten days of August expresses the highest yields and reduces the gaps for both locations.